The role of electronic word of mouth (e-WOM), online customer review, and micro influencer in influenced purchase decision on Tiktok Shop - Farel Abisha Raya; Sri Sudarsi (Journal of Management Small and Medium Enterprises (SMEs), 2026)
The rapid growth of social commerce, particularly TikTok Shop, has transformed consumer purchasing behavior. Purchase decision are no longer influenced solely by seller-provided information but also by EWOM, Online Customer Reviews, and Micro Influencers. This study examines the influence of these three factors on Purchase Decision among TikTok Shop users. A quantitative survey approach was employed using primary data collected from 100 respondents through purposive sampling. Data were analyzed using multiple linear regression with SPSS, including validity, reliability, classical assumption, coefficient of determination, F-test, and t-test analyses. The findings indicate that EWOM, Online Customer Reviews, and Micro Influencers have positive and significant effects on Purchase Decision, both individually and simultaneously. E-WOM is the most influential variable. The Adjusted R Square value of 0.620 indicates that 62% of the variation in Purchase Decision is explained by the three independent variables, while the remaining 38% is explained by other factors. Keywords: Electronic Word of Mouth (E-WOM); Online Customer Review; Micro Influencer